Tracing dust input to the global ocean using thorium isotopes in marine sediments: ThoroMap. Issue 10 (29th October 2016) - Kienast, S. S.; Winckler, G.; Lippold, J.; Albani, S.; Mahowald, N. M.
Abstract: Continental dust input into the ocean‐atmosphere system has significant ramifications for biogeochemical cycles and global climate, yet direct observations of dust deposition in the ocean remain scarce. The long‐lived isotope thorium‐232 ( 232 Th) is greatly enriched in upper continental crust compared to oceanic crust and mid‐ocean ridge basalt‐like volcanogenic material. In open ocean sediments, away from fluvial and ice‐rafted sources of continental material, 232 Th is often assumed to be of predominantly eolian origin. In conjunction with flux normalization based on the particle reactive radioisotope thorium‐230 ( 230 Th), 232 Th measurements in marine sediments are a promising proxy for dust accumulation in the modern and past ocean. Here we present ThoroMap, a new global data compilation of 230 Th‐normalized fluxes of 232 Th. After careful screening, we derive dust deposition estimates in the global ocean averaged for the late Holocene (0–4 ka) and the Last Glacial Maximum (LGM, 19–23 ka). ThoroMap is compared with dust deposition estimates derived from the Community Climate System Model (CCSM3) and CCSM4, two coupled atmosphere, land, ocean, and sea ice models. Model‐data correlation factors are 0.63 (CCSM3) and 0.59 (CCSM4) in the late Holocene and 0.82 (CCSM3) and 0.83 (CCSM4) in the LGM. ThoroMap is the first compilation that is built on a single, specific proxy for dust and that exclusively uses flux‐normalization to derive dust deposition rates. Key Points: Continental dust input to the ocean is reconstructed using thorium isotopes A new global data base of dust fluxes is presented for the late Holocene and the Last Glacial Maximum Comparisons with recent coupled models identify regions of good model‐data agreement